Evaluation of Fifteen Cultivars of Cool‐Season Perennial Grasses as Biofuel Feedstocks Using Near‐Infrared. (1st September 2017) - Payne, Courtney; Wolfrum, Edward J.; Nagle, Nick; Brummer, Joe E.; Hansen, Neil
Abstract : Core Ideas: Harvest yield varies more across species than sugar content and accessibility. Harvest yield and sugar accessibility are both critical parameters for conversion. Near‐infrared/partial least square models are valuable for quickly evaluating biomass for bioconversion. Cool‐season (C3) perennial grasses have a long history of cultivation and use as animal forage. This study evaluated 15 cultivars of C3 grasses, when harvested in late June for increased biomass yield, as biofuel feedstocks using near‐ infrared spectroscopy (NIR) based partial least square (PLS) analysis. These grasses were grown near Iliff, CO, for three growing seasons (2009–2011). The carbohydrate composition and released carbohydrates (total glucose and xylose released from dilute acid pretreatment and enzymatic hydrolysis [EH]) were predicted for samples from the study using NIR/PLS. The results were analyzed from a biofuels perspective, where composition combined with harvest yield provided information on the carbohydrate yield available for biomass conversion processes, and released carbohydrate yield provided information on the accessibility of those carbohydrates to conversion methods. The range in harvest yields varied more among cultivars (2900 kg ha −1 ) than did the range in carbohydrate composition (56.0 g kg −1 ) or released carbohydrates (60.0 g kg −1 ). When comparing carbohydrate yield to released carbohydrate yield between cultivars, an efficiency as high as 87% release of available carbohydrates was obtained for pubescent wheatgrass [ Thinopyrum intermedium (Host) Barkworth & D.R. Dewey 'Mansaka'], with a low of 71% for hybrid wheatgrass [ Elytrigia repens (L.) nevski ´ pseudoroegneria spicata (PURSH) A. Love 'Newhy']. Though hybrid wheatgrass had the lowest release efficiency, its high harvest yield resulted in release of more total carbohydrates than half the other cultivars analyzed. This suggested that harvest yield, carbohydrate release, and carbohydrate composition, togetherplay significant roles in biofuel feedstock evaluation.